Pelindungan Hukum terhadap Korban Revenge Porn sebagai Bentuk Kekerasan Berbasis Gender Online Ditinjau dari Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual - Azza Fitrahul Faizah; Muhammad Rifqi Hariri (Jurnal Hukum Lex Generalis, 2022)
During the Covid-19 pandemic, there was an increase in cases of Online Gender-Based Violence (KBGO), especially cases of Revenge Porn. The passing of the Sexual Assault Act seems to be a breath of fresh air in the prevention, handling, and recovery of victims of sexual violence. Therefore, it is necessary to conduct a study to examine the potential effectiveness of the Sexual Assault Act in handling and preventing KBGO in Indonesia. This journal article uses a normative juridical approach with descriptive-analytical specifications. The results of the study indicate that the Sexual Assault Act provides a positive signal for the prevention and handling of cases of sexual violence in Indonesia. However, the government needs to form implementing regulations so that these regulations can be implemented properly by law enforcers.